رۆڵی ماڵپەڕە ئەلیکترۆنییە کوردییەکان لە پێکهێنانی هۆشیاریی سیاسیی لە هەرێمی کوردستاندا: توێژینەوەیەکی مەیدانییە - موڕاد, پ. د. هێرش رەسوڵ; مستەفا, دانا بەهادین (Sulaimani Journal for Humanities, 2023)
Nowadays, Websites are a new media tool that can play a role in many aspects of life and society, including politics. As Political awareness is one of the consequences that can be achieved through the media in general and websites. This study; it aims to study the role of political articles in Kurdish websites in the formation of political awareness in the Kurdistan Region on three aspects related to the same issue: (political information, political thought and political analytics). To achieve this main goal, researchers used descriptive and survey methods. The research community includes all lecturers of colleges of Sulaimani Polytechnic University, a sample of (114) lecturers of these colleges. In conclusion, at the end of the study, the researchers reached several of conclusions, including: A handful of the study, to a significant extent and continuously watched and followed (political) subjects, among them, were more recipients of (political news, reports and interviews). In contrast; (Articles, photo journals, political advertisements) are less viewed. The formation of political awareness through websites has different dimensions: (presentation of political information, political thought, and political analytics) in their political articles, including; Kurdish websites have played a role at different levels, in some areas more and in others less.
Keywords: Role; Kurdish websites; Political materials; Formation; Political awareness; Iraqi Kurdistan Region